European mammal turnover driven by a global rapid warming event preceding the Paleocene–Eocene Thermal Maximum - Rodolphe Tabuce; Bernard Marandat; Sylvain Adnet; Killian Gernelle; Flavia Girard; Laurent Marivaux; Floréal Solé; Johann Schnyder; Etienne Steurbaut; Jean-Yves Storme; Monique Vianey-Liaud; Johan Yans (Proceedings of the National Academy of Sciences, 2025)
A brief global warming event known as the Pre-Onset Excursion (POE) occurred just before the Paleocene–Eocene Thermal Maximum (PETM, 56 Mya). The deconvolution of the evolutionary consequences of these two hyperthermal events is puzzling because of their close temporal proximity and the lack of comprehensive, well-calibrated paleontological records, especially in terrestrial environments. As a consequence, the impact of the POE on mammalian evolution and its role in shaping PETM faunas remains unclear. Here, we report from France a mammalian fauna, named Albas, which is interpreted to postdate the POE and predate the PETM. The absence of artiodactyls, perissodactyls, and euprimates at Albas lends support to the controversial hypothesis that these “modern” mammal groups appeared in the European fossil record during the PETM. In contrast, Albas yielded the European first definitive Paleocene record of metatherians, paromomyid primates, “creodonts,” and rodents, challenging the assumption that these groups migrated into Europe during the PETM. Because the majority of them originated from North American pre-POE species, we tentatively suggest that these “precursor” dispersers entered Europe during the POE. Similar to the modern orders during the PETM, these “precursor” dispersers likely entered Europe through corridors in the continuous evergreen forest belt at high latitudes. Our findings highlight how a brief warming event in the Arctic during the latest Paleocene, such as the POE (which could result in a release of carbon into the atmosphere similar to cumulative ongoing anthropogenic emissions), significantly influenced the evolutionary dynamics of European mammals.